Numerical simulation of surface topography and residual stress after abrasive water jet sequential peening. (April 2021) - He, Zhanshu; Cui, Beibei; Zhao, Shusen; Liu, Zhihua; Yu, Jinlong; Li, Chao; Yu, Huixin; Chen, Lei
In this paper, the theoretical models of the surface topography and residual stress (RS) were proposed, and the abrasive water jet sequential peening (AWJSP) finite element models were established by using ABAQUS. Then, the formation mechanism of the surface topography in multiple passes AWJSP process and the coupling mechanism of RS in a single and multiple passes AWJSP process were analyzed. After that, the influence of the number of shots (i.e. N ), the distance between the center of adjacent shots Dc, shot velocity v, and shot radius R on the surface topography and residual stress field (RSF) of the target were investigated. Results show that successive dimples were formed by single-pass AWJSP, the RSF formed by the impact of each shot will influence the previous RSF, and that will be coupled with it. In multiple passes AWJSP process, decreasing Dc can decrease the surface roughness, the surface smoothness of the target material will gradually become better, and the RSF will also be uniform. Under full coverage condition, the surface roughness Rt and mean width of the profile Rsm will gradually decrease with the decrease of Dc, while the change of Dc has little influence on the RSF. Increasing the v can increase Rt and Rsm, and it is beneficial to induce a large and deep compressive RS layer. Increasing the R can decrease Rt, Rsm remains unchanged, and it is beneficial to induce a deep compressive RS layer.